Development of Pop-Up Book Media for Introducing Sexual Education to Children Aged 5–6 Years - Rusady, Paramita; Fitriani, Wahidah; Raza, Amir (CV Berkah Syahdin Trust, 2025)
Purpose – This study aims to develop a pop-up book as an educational medium to introduce sexual education concepts appropriately to children aged 5–6 years, in order to support their understanding of body awareness, personal boundaries, and safe behavior from an early age. Design/methods/approach – This research employed a Research and Development (R&D) approach utilizing the 4D model (Define, Design, Develop, and Disseminate) proposed by Thiagarajan, et al., though the study was limited to the development phase. Primary data were collected through expert validation and practitioner feedback using structured validity and practicality instruments. The validity instrument assessed three domains: graphic design feasibility, content relevance, and media suitability. The practicality instrument evaluated media usability from the perspectives of content clarity and instructional effectiveness. Findings – The developed pop-up book media obtained a validity score of 76.33%, indicating a valid category, and a practicality score of 81.33%, indicating a highly practical category. These results confirm that the media is both pedagogically sound and feasible for implementation in early childhood learning contexts, particularly for delivering sensitive topics such as sexual education in a developmentally appropriate and engaging manner. Research implications/Limitations – This study is limited to the development phase; thus, future research is recommended to explore the effectiveness of the pop-up book in improving children's knowledge, attitudes, and protective behaviors related to sexual education through experimental or longitudinal studies. Originality/value – This study presents an innovative, developmentally appropriate approach to introducing sexual education through pop-up book media, offering a practical solution for early childhood educators to address sensitive topics in an engaging and culturally respectful manner.